Are the field tests related to the match running distance and the technical performance in young soccer players? - Zachariadis, M. D.; Koutlianos, N.; Michailidis, Y.; Mandroukas, A.; Vardakis, L.; Mavrommatis, G.; Christoulas, K.; Metaxas, T. (Trends in Sport Sciences, 2020)
Introduction. A lot of studies have demonstrated the relationships between filed tests and match running performance in soccer players, but the impact of anthropometric characteristics and physical performance on technical abilities remains unclear. Aim of Study. The aim of this study was to examine the influence of physical performance on the technical abilities and match running performance of 20 young soccer players (U15) during soccer games. Material and Methods. Anthropometric profile, sexual-maturity assessment and physical performance tests (sprint tests, countermovement jump, squat jump, standinglong jump, multiple 5-bound test, sit & reach test, change of direction, and Yo-Yo intermittent endurance test level 1 - IE1) were conducted 3 weeks before the first of 10 soccer matches. Technical performance was determined by the frequency of actions during the 10 soccer games. Distance covered during matches was recorded using GPS devices. Results. The distance covered at speeds of 15.8-19.7 km/h correlated with performance in the long jump and Yo-Yo test (r = 0.49, P = 0.034, and r = 0.59, P = 0.008, respectively). The distance covered at higher speeds (19.8-24 km/h) correlated with performance in squat jump test and Yo-Yo test (r = 0.49, P = 0.032, and r = 0.50, P = 0.030, respectively). Factor analysis identified three technical actions of the highest importance: total activity, possession game, and attempts for goal. Multivariate canonical correlation analysis, used to verify the prediction of a multiple dependent variable set from field tests, showed that our model was not well a ajusted. Conclusions. The current data suggest that the selected set of independent variables might not be useful in predicting technical performance in young soccer players. When we have the opportunity to select a young soccer player we have to use many fitness, technique, tactical and psychomotor tests to evaluate him. However, the Yo-Yo IE1 test was correlated to match running performance so it can be used by the trainers to predict match running performance of their young players.